2014
DOI: 10.1590/1413-81232014191.2000
|View full text |Cite
|
Sign up to set email alerts
|

Associação entre circunferência da cintura e índice de massa corporal de mulheres brasileiras

Abstract: Associação entre circunferência da cintura e índice de massa corporal de mulheres brasileiras: PNDS 2006Association between waist circumference and body mass index of Brazilian women: NDHS 2006 Resumo O objetivo do estudo foi analisar a associação entre a circunferência da cintura (CC)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0
5

Year Published

2017
2017
2019
2019

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 21 publications
0
14
0
5
Order By: Relevance
“…Abdominal obesity assessed by waist circumference (WC) is related to a higher risk of mortality (Meller et al, 2014). This reflects the accumulation of visceral fat directly related to the genesis of the metabolic syndrome by promoting insulin resistance, glucose intolerance and a chronic inflammatory state.…”
Section: Resultsmentioning
confidence: 99%
“…Abdominal obesity assessed by waist circumference (WC) is related to a higher risk of mortality (Meller et al, 2014). This reflects the accumulation of visceral fat directly related to the genesis of the metabolic syndrome by promoting insulin resistance, glucose intolerance and a chronic inflammatory state.…”
Section: Resultsmentioning
confidence: 99%
“…In Brazil, Meller et al 30 conducted a study with adult women and found that one out of four women without overweight had a WC > 80 cm. Similar results were observed in a study conducted in Maranhão 31 , which found 15.5% of abdominal obesity in eutrophic women.…”
Section: Discussionmentioning
confidence: 99%
“…No Brasil, Meller et al 30 realizaram estudo com mulheres adultas, sendo constatado que uma em cada quatro mulheres sem excesso de peso apresentavam CC > 80 cm. Resultados semelhantes foram observados em estudo realizado no Maranhão 31 , que encontrou 15,5% de obesidade abdominal em mulheres eutróficas.…”
Section: Discussionunclassified
“…MELLER et al, (2006) concluíram em estudo que a elevada prevalência de mulheres com IMC elevado, implica na necessidade de políticas públicas de saúde que visem não somente a prevenção e o tratamento do excesso de peso, mas também da obesidade abdominal, a fim de promover o estado nutricional adequado e reduzir as prevalências das doenças associadas. Neste estudo, todos os voluntários apresentaram CA maior que 97 cm, que associado aos elevados valores de IMC observados, confere alto risco a problema de saúde associados a essa parcela da população.…”
Section: Discussionunclassified